2021
DOI: 10.1177/08912432211057916
|View full text |Cite
|
Sign up to set email alerts
|

School as a Hostile Institution: How Black and Immigrant Girls of Color Experience the Classroom

Abstract: The paradox of girls’ academic gains over boys, across race and class, has perplexed scholars for the last few decades. Through a 3-year longitudinal ethnography of two predominantly economically marginalized and racially minoritized schools, I contend that while racially marginalized girls may have made academic gains, school is nevertheless a hostile institution for them. Focusing on the case of Black girls and recent immigrant girls of color, I identify three specific ways in which school functions as hosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Even as "good Latinx" narratives legitimated Latinx youths' access to greater resources, including mental health services, educators mobilized other discourses that not only homogenized Latinidad but also cast Latinxs as deficient in some way. While extant literature highlights that newcomer immigrants often exhibit "better" behavior or appear more "deserving" than native-born peers (Ray, 2022;Valenzuela, 1999), this study reveals educators linking Latinidad with emotional excessiveness in newly arrived non-Black Latinx youth, striving to mold them into the "good Latinx" subject. While similar to the racialized depiction of Black youth as unmotivated or aggressive, the key difference is that even the perceived deficiency of Latinidad allows access to resources, albeit with simultaneous marginalization.…”
Section: Constrained Credentials: Conditional Access To Educational A...mentioning
confidence: 72%
“…Even as "good Latinx" narratives legitimated Latinx youths' access to greater resources, including mental health services, educators mobilized other discourses that not only homogenized Latinidad but also cast Latinxs as deficient in some way. While extant literature highlights that newcomer immigrants often exhibit "better" behavior or appear more "deserving" than native-born peers (Ray, 2022;Valenzuela, 1999), this study reveals educators linking Latinidad with emotional excessiveness in newly arrived non-Black Latinx youth, striving to mold them into the "good Latinx" subject. While similar to the racialized depiction of Black youth as unmotivated or aggressive, the key difference is that even the perceived deficiency of Latinidad allows access to resources, albeit with simultaneous marginalization.…”
Section: Constrained Credentials: Conditional Access To Educational A...mentioning
confidence: 72%
“…Black girls also encounter misunderstandings and invisibility in STEM education, impeding their participation and success in these fields (Wang, Henry, Wu, Del Toro, and Huguley, 2020). Furthermore, they are often subjected to sexual harassment and their intellectual contributions are erased or devalued in the classroom (Ray, 2022).…”
Section: The Problems In Public Schoolsmentioning
confidence: 99%
“…The idea of monolithic Black female identity needs to be de-constructed. A specific focus on the Black immigrant women's college experience in engineering appears to be lacking within the literature even though there are some studies dedicated to Black immigrant students' experiences in education [10,11] Even though this space is not much explored, recently, a research study revealed that Black and immigrant girls of color experienced gendered racial harassment, erasure of intellect, and hostility in school [12]. The research questions guiding this study are: What are the experiences of utilizing available on-campus support of the Black immigrant women pursuing Engineering?…”
Section: Introductionmentioning
confidence: 99%
“…According to a study, Black girls and immigrant girls were twice more likely to repeat a grade, be suspended, and be expelled than their White female and White male peers before even acquiring a high school diploma [10]. We expanded on the Critical Race Feminism framework and introduced immigration status and socio-economic status as marginalized intersectional identities that interact with race and gender.…”
Section: Introductionmentioning
confidence: 99%